Prevalence of High Blood Pressure in Pregnant Women in Aljouf, Saudi Arabia - Umme Salma; Ahmed Alshaikh; Fawaz Edris; Md Sayed Sheikh; Eman Rashwan (AlQalam Journal of Medical and Applied Sciences, 2023)
In frontline healthcare settings, there aren’t enough studies on its prevalence and associated factors. Our goal was to assess the prevalence of HBP and its risk factors among pregnant women in the Aljouf area. A cross-sectional study conducted in the obstetrics department of Maternity and Children Hospital (MCH) Sakaka, Aljouf, Saudi Arabia, included a pregnant woman with high blood pressure (HBP). A multivariable logistic regression analysis was used to determine the causes of HBP. A bout 451 pregnant women with high blood pressure were included among 3750 other pregnant women. In general, the prevalence of HBP was 12% (95% confidence interval [CI] 0.7-2.3); among women, it was 0.7% (95% CI 0.3-1.1), 1.6% (95% CI 0.8-2.1), and 3% (95% CI 1.2-8.6) in the first, second, and third trimesters, respectively. Trimester of pregnancy, age, income, occupation, and parity, were not linked to HBP during pregnancy in the multivariable analysis. HBP was present in 12% of pregnant women in the Aljouf region, which is considered to be of moderate-high prevalence. High blood pressure during pregnancy can harm both the mother and the fetus. As a result, the prevalence research has the benefit of encouraging medical professionals to conduct early screening, which helps with prevention, treatment, and also decreases the burden of negative pregnancy outcomes. ارتفاع ضغط الدم أثناء الحمل قد يؤدي إلى وفاة الأم والجنين. في إعدادات الرعاية الصحية في الخطوط الأمامية، لا توجد دراسات كافية حول مدى انتشاره والعوامل المرتبطة به. كان هدفنا هو تقييم مدى انتشار مرض HBP وعوامل الخطر المرتبطة به بين النساء الحوامل في منطقة الجوف. شملت دراسة مقطعية أجريت في قسم التوليد بمستشفى الولادة والأطفال (MCH) سكاكا، الجوف، المملكة العربية السعودية، امرأة حامل تعاني من ارتفاع ضغط الدم (HBP). تم استخدام تحليل الانحدار اللوجستي متعدد المتغيرات لتحديد أسباب .HB تم تضمين حوالي 451 امرأة حامل تعاني من ارتفاع ضغط الدم من بين 3750 امرأة حامل أخرى. بشكل عام، كان معدل انتشار HBP 12% (فاصل الثقة 95% [CI] 0.7-2.3)؛ بين النساء، كان 0.7٪ (95٪ CI 0.3-1.1)، 1.6٪ (95٪ CI 0.8-2.1)، و 3٪ (95٪ (CI 1.2-8.6) في الأشهر الثلاثة الأولى والثانية والثالثة، على التوالي. لم يتم ربط الأشهر الثلاثة من الحمل والعمر والدخل والمهنة والتكافؤ بـ HBP أثناء الحمل في التحليل متعدد المتغيرات. كان مرض HBP موجودًا في 12% من النساء الحوامل في منطقة الجوف، وهو ما يعتبر ذو انتشار متوسط إلى مرتفع. ارتفاع ضغط الدم أثناء الحمل يمكن أن يضر الأم والجنين. ونتيجة لذلك، فإن أبحاث الانتشار لها فائدة تتمثل في تشجيع المهنيين الطبيين على إجراء الفحص المبكر، مما يساعد في الوقاية والعلاج، ويقلل أيضًا من عبء نتائج الحمل السلبية